The Mirror in Art: Vanitas, Veritas, and Vision - Helena Goscilo (Studies in 20th & 21st Century Literature, 2010)
Humankind’s venerable obsession with the mirror, traceable to the ancient myths of Medusa and Narcissus, is copiously attested in Western art, which historically relied on the mirror as both practical tool and polysemous trope. While the mirror’s reflective capacities encouraged its identification with the vaunted mimetic function of literature and film, its refractive quality enabled artists to explore and comment on perspective, in the process challenging the concept of art’s faithful representation of phenomena. My radically compressed and selective overview of the mirror’s significance in Western iconography focuses primarily on visibility, gaze, and gender, dwelling on key moments and genres that most vividly illustrate the paradoxes of the mirror as both symbol and utilitarian object. Comparing Russian art with its Western counterpart, I argue that Russia’s distinctive iconographic traditions account for Russian divergences from major aspects of the inherited and evolving mirror rhetoric that prevailed in Western Europe.
Keywords: Medusa; Narcissus; mirror; Western art; reflection; refraction; perspective; visibility; gaze; gender; Russian Art; Literature; Film